Son of a witch : [compact disc, unabridged] : a novel - Maguire, Gregory (Maguire, Gregory. Wicked years, 2005)
In the land of Oz, after Dorothy has detroyed the witch, an adolescent boy named Liir, who may be the witch's son, is willed back to life at the Cloister of Saint Gilda.